ANALYSIS OF CHARACTER AND CHARACTERIZATION IN ERNEST MILLER HEMINGWAY NOVEL THE OLD MAN AND THE SEA - Heru, Fransiskus (English Language Education Study Program, 2023)
Based on the novel The Old Man and The Sea by Ernest Hemingway, 1952. The discussion of the problem in this novel is to analyze the main characters, namely Santiago, Manolin and Marlin. The data used to strengthen the facts in this study are library research and are supported by novels and biographies of the author. The method used in this research is a comparative literature study with descriptive qualitative research. The characterizations contained in these characters are as follows: Santiago is a character who has a physical condition, is generous, never gives up, a parent figure for manolin, an unlucky character (salao). Meanwhile, Manolin is a character who has unyielding character, lucky character, compassionate and kind, loyal character. As for the non-human character, he is Marlin, besides he is a friend and brother to Santiago, stubborn, Santiago's pride.